Adaptive Testing for Specification Coverage in CPS Models. Issue 5 (2021) - Bartocci, Ezio; Bloem, Roderick; Maderbacher, Benedikt; Manjunath, Niveditha; Ničković, Dejan
Abstract: Ensuring correctness of cyber-physical systems (CPS) is a challenging task that is in practice often addressed with simulation-based testing. Formal specification languages, such as Signal Temporal Logic (STL), are used to mathematically express CPS requirements and thus render the simulation activity more principled. We propose a novel method for adaptive generation of tests with specification coverage for STL. To achieve this goal, we devise cooperative reachability games that we combine with numerical optimization to create tests that explore the system in a way that exercise various parts of the specification. To the best of our knowledge our approach is the first adaptive testing approach that can be applied directly to MATLAB™ Simulink/Stateflow models. We implemented our approach in a prototype tool and evaluated it on several illustrating examples and a case study from the avionics domain, demonstrating the effectiveness of adaptive testing to (1) incrementally build a test case that reaches a test objective, (2) generate a test suite that increases the specification coverage, and (3) infer what part of the specification is actually implemented.